Implementation of an Image Processing System in Drone Battle Based on Ardupilot - Wikan Pambudi; M Rizky Fitri Padillah (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
The aim of this research is to create an ArduPilot-based image processing system for drone combat that can detect, identify and track targets in real-time to improve navigation capabilities and combat strategies. This system will integrate drone hardware with image processing algorithms and cameras to detect target position and movement. Tests show that detection and maneuvering in dynamic combat conditions are better. It is hoped that this implementation will be an innovative solution for drone combat and additional applications such as surveillance and rescue missions.